Investigation of the Dose-Enhancement Effects of Spherical and Rod-Shaped Gold Nanoparticles on the HeLa Cell Line: - Amani, Samad; Mehdizadeh, Alireza; Movahedi, Mohammad Mehdi; Keshavarz, Marzieh; Koosha, Fereshteh (Galen Medical Journal, 2020)
Background: Cervical cancer cells are known as radioresistant cells. Current treatment methods have not improved the patientsâ€™ survival efficiently; thus, new therapeutic strategies are needed to enhance the efficacy of radiotherapy. Gold nanomaterials with different shapes and sizes have been explored as radiosensitizers. The present study compared the radiosensitizing effects of gold nanorods (AuNRs) with spherical gold nanoparticles (AuNPs) on the HeLa cell line irradiated with megavoltage X-rays. Materials and Methods: The cytotoxicity of AuNRs and AuNPs on HeLa cells in the presence and absence of 6-MV X-ray was investigated using the MTT assay. For this aim, HeLa cells were incubated with and AuNPs and AuNRs at various concentrations (5, 10, and 15 Âµg/mL) for 6 hours. Afterward, HeLa cells were irradiated with 6-MV X-ray at a single dose of 2 Gy. Results: The results showed that the addition of AuNRs and AuNPs could enhance the radiosensitivity of HeLa cells. Both AuNRs and AuNPs showed low toxicity on HeLa cells, while AuNRs were more toxic than AuNPs at the examined concentrations. Moreover, it was found that AuNRs could enhance the radiosensitivity of HeLa cells more than spherical-shaped AuNPs. Conclusion: This study revealed that the shape of nanoparticles is an effective factor when they are used as radiosensitizing agents during radiotherapy. [GMJ.2020;9:e1581]